The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bjsports-2018-099700
|View full text |Cite
|
Sign up to set email alerts
|

Serum androgen levels are positively correlated with athletic performance and competition results in elite female athletes

Abstract: We thank our colleagues for their constructive comments that relate to our two articles in the July 2017 issue of BJSM. Bermon and Garnier StudyThe main criticisms expressed about the data used and our statistical analysis were (1) our 'concentration' on free testosterone (fT) rather than total testosterone (T) 3 (presumably because the T results were only presented in the Internet version of the paper), (2) the fact that 17.3% of the athletes were sampled at both World Championships (Daegu and Moscow), 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…In 2015, the regulations were challenged by an athlete in the Court of Arbitration of Sport (CAS), which then suspended them pending further scientific evidence concerning the influence of testosterone levels in the male range on the athletic performance of women. In response, recent observational data (58,59,60), as well as our RCT described, (55) have provided additional evidence for the performance-enhancing effects of testosterone in female athletes.…”
Section: Regulations Concerning the Eligibility To Compete As A Womanmentioning
confidence: 62%
See 1 more Smart Citation
“…In 2015, the regulations were challenged by an athlete in the Court of Arbitration of Sport (CAS), which then suspended them pending further scientific evidence concerning the influence of testosterone levels in the male range on the athletic performance of women. In response, recent observational data (58,59,60), as well as our RCT described, (55) have provided additional evidence for the performance-enhancing effects of testosterone in female athletes.…”
Section: Regulations Concerning the Eligibility To Compete As A Womanmentioning
confidence: 62%
“…One earlier report including female athletes (n = 22) demonstrated that serum levels of testosterone at rest were positively correlated with explosive performance (the vertical jump test) (57). A much larger study involved more than a 1000 elite female participants in the 2011 and 2013 International Association of Athletics Federations (IAAF) World Championships (58,59), of whom only 1.8% had clearly elevated levels of testosterone indicative of DSD or doping. These athletes were classified in tertiles on the basis of their levels of testosterone, and the performance in those in the highest tertile in the 400-m race, 400-m hurdles and 800-m race was found to be 2.1-2.5% better than that of those in the lowest tertile.…”
Section: The Influence Of Endogenous Androgens On the Physical Performentioning
confidence: 99%
“…Following the release of a subset of those data, the independent researchers calculated errors in the data ranging from 17-33 per cent for four of the regulated events (400m, 400H, 800m, and 1500m) and called for the study to be retracted (Pielke 2018;Longman 2018). Days before the independent researchers submitted their re-analysis, Bermon and colleagues released their own re-analysis of the data (Pielke 2018;Bermon et al 2018). performance advantage^when it is between 5 and 10 nmol/L (IAAF 2018c, 5).…”
mentioning
confidence: 99%
“…The IAAF duly commissioned further research (Bermon et al, 2018; Bermon and Garnier, 2017 [16,17]) the results of which were clearly insufficient, even on the IAAF's own interpretation, to convince the CAS that the performance advantage was of the same magnitude as male athletes or significant across all athletic events. Accordingly, the Hyperandrogenism Regulations were dropped and a variation was introduced that was drafted to focus on certain events where the evidence of performance advantage was deemed by the IAAF to be significant.…”
Section: Classification By Sex and Regulation Of Eligibility To Compementioning
confidence: 99%
“…However, from the historical background to the Testosterone Regulations and from the scientific evidence on which the IAAF purports to rely, that does not appear to be the approach that has been taken. For example, in the Bermon and Garnier studies (Bermon et al, 2018; Bermon and Garnier, 2017 [16,17]) on which heavy reliance is placed, the data in relation to male performance differences based on testosterone levels is far less than the female data (the female data is taken from both the Daegu and Moscow IAAF world championships, but the Daegu world championships is not used in relation to male athletes) and there is a fairly blunt conclusion that there is no significant performance difference between the males with low testosterone levels and those with high levels. Since the whole basis of the Testosterone Regulations is that increased testosterone does provide a performance advantage, it seems strange that the IAAF have not sought to explain or investigate this further, especially given that other academic evidence relied on by the IAAF suggests increases in testosterone in healthy adult males increases muscle strength and size in a linear fashion (Auchus, 2018 [9]).…”
Section: The Problem With Integrity Solidarity and Fair Playmentioning
confidence: 99%